The inner disk and accretion flow of the close binary DQ Tau - Muzerolle Page, James; Balog, Zoltan (The astrophysical journal, 2019)
We present multiepoch optical and near-infrared (NIR) photometry and spectroscopy of the spectroscopic binary T Tauri star DQ Tau. The photometric monitoring, obtained using SMARTS ANDICAM, recovers the previously seen correlation between optical flux and the 15.8 day binary orbital period, with blue flux peaks occurring close to most observed periastron passages. For the first time, we find an even more consistent correlation between orbital period and NIR brightness and color. The onset of pulse events in the NIR precedes those in the optical by a few days, on average, with the rise usually starting near apastron orbital phase. We further obtained five epochs of spectroscopy using Infrared Telescope Facility (IRTF) SpeX, with a wavelength range of 0.8-5 μm, and derived spectra of the infrared excess emission. The shape and strength of the excess varies with time, with cooler and weaker characteristic dust emission (T ∼ 1100-1300 K) over most of the binary orbit, and stronger/warmer dust emission (T ∼ 1600 K, indicative of dust sublimation) just before periastron passage. We suggest that our results are broadly consistent with predictions of simulations of disk structure and accretion flows around close binaries, with the varying dust emission possibly tracing the evolution of accretion streams falling inward through a circumbinary disk cavity and feeding the accretion pulses traced by the optical photometry and NIR emission lines. However, our results also show more complicated behavior that is not fully explained by this simple picture, and will require further observations and modeling to fully interpret.
Gesehen am 04.06.2019